2011
DOI: 10.1007/s11250-011-9882-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of superantigenic toxin genes in Staphylococcus aureus strains from subclinical bovine mastitis

Abstract: The aim of this study was to determine the presence of genes encoding enterotoxins (sea-sej) and toxic shock syndrome toxin-1 (tst) of Staphylococcus aureus strains (n = 130) isolated from subclinical bovine mastitis in Turkey by polymerase chain reaction. Sixty-one (46.9%) isolates were found to contain one or more toxin genes. The most frequently found enterotoxin genes were seg (16.2%) and sei (16.2%), followed by sec (15.4%), sed (10.8%), and sej (10.8%), respectively. The tst gene was detected in seven (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
4
15
0
4
Order By: Relevance
“…A high incidence of seg-sei genes was also found. It had been previously reported that the sei gene was common in isolates from subclinical bovine mastitis (15) and retail meats (36). In this study, this gene was also present in all strains from the seafood industry.…”
Section: Discussionsupporting
confidence: 69%
“…A high incidence of seg-sei genes was also found. It had been previously reported that the sei gene was common in isolates from subclinical bovine mastitis (15) and retail meats (36). In this study, this gene was also present in all strains from the seafood industry.…”
Section: Discussionsupporting
confidence: 69%
“…Nineteen of 102 S. aureus isolates (18.6%) recovered from BTM and milk filters from national milk-producing herds in Ireland showed the presence of one or more enterotoxin genes (44). Conversely, a higher percentage of isolates, 46.9% of 130, associated with subclinical bovine mastitis in Turkey showed the presence of one or more enterotoxin genes (23). The aim of the present study was to characterize and document the prevalence and distribution of MSSA and MRSA in bulk tank milk samples.…”
mentioning
confidence: 99%
“…Nos estudos realizados no nordeste tão pouco foram encontrados isolados de S. aureus portadores deste gene (Almeida et al 2013, Ferreira et al 2014, Silveira-Filho et al 2014. Em outros paí-ses também são descritos estudos onde a frequência deste gene é cero nos isolados de S. aureus circulantes, por exemplo na Itália (Perillo et al 2012, Ruaro et al 2013, Turquia (Günaydın et al 2011) e no Estado da Califórnia (USA) (Cenci-Goga et al 2003). A toxina SEB é considerada uma arma biológica e sua inalação pode provocar lesões pulmonares e insuficiência respiratória (Rao et al 2014).…”
Section: Discussionunclassified
“…No Estado da Paraí-ba, o gene que codifica para essa toxina não foi detectado (Ferreira et al 2014). Internacionalmente também não foi encontrado o gene seh em isolados de S. aureus causadores de mastite bovina na Turquia (Günaydın et al 2011) em leite de ovelhas na Itália (Perillo et al 2012) ou são relatadas frequência baixa (1,7%) na Bélgica (Ote et al 2011).…”
Section: Discussionunclassified